Resilient wide‐area monitoring and protection scheme with IEEE Std. C37.118.1‐2011 criteria for complex smart grid system using phase diagram. Issue 2 (26th April 2019) - Eissa, Moustafa M.
Abstract : Challenges facing power system protection in a wide‐area system are latency and full coverage of a wide‐area disturbance. The complexity of large‐scale power system configurations has led to challenges in the design of coordination and operating systems for protection relays. Local measurements used for primary and backup protection cannot consider wide system disturbances. A new wide‐area‐monitoring‐system‐based primary protection is presented for a complex power system involving double and single lines. It is based on describing the non‐linear dynamic operation of the transmission lines during a fault in the form of a set of differential equations that are solved through paths movements in a phase diagram. The fault on the lines can be precisely recognised. The speed of the traditional communication media limits wide‐area monitoring as backup protection. This study presents the primary protection scheme for double and single circuits in a wide area for the first time based on fourth‐generation technology with low latency. The justification for applying the proposed scheme as primary protection in a wide‐area‐monitoring system is discussed. The number of relays on the studied configuration is reduced from 18 local relays to only 5 phasor measurement units for protecting the lines in the area.